THE EFFECT OF GRATITUDE AND ACADEMIC SELF EFFICACY ON ACADEMIC ENGAGEMENT IN STUDENTS - Yudiani, Ema; Khosiyah, Siti; Umer, Abad (Psikis : Jurnal Psikologi Islami, 2023)
Engagement plays an important role in academic success and in the world of work, it is a hallmark of an optimal learning experience (Bilge, Tuzkol, Dots, & Cetin, 2014). Engaged students usually do well in their studies (Kuh, Kinzie, Buckley, Bridges, & Hayek, 2007; Salanova, Schaufeli, Martinez, & Breso, 2010). Therefore, academic engagement is needed for students, so that the objectives of the academic process activities can be achieved effectively and efficiently. This study aims to determine the effect of gratitude, academic self-efficacy, on academic engagement. The sample in this study were students of the Faculty of Psychology, Raden Fatah State Islamic University Palembang with a total population of 968 students. The sample in this study amounted to 155 students of the psychology faculty. The sampling technique in this study uses a non probability sampling technique, which means that not all students have the same opportunity to be used as research samples. Data analysis will be carried out by linear regression analysis at a significance level of 0.005, using the SPSS.20 application. The results showed that there was a significant effect of gratitude, academic self-efficacy academic engagement (R2 = 29.4%). The results of the hypothesis test show that gratitude and academic self-efficacy have a significant effect on academic engagement.